The Monroe Declaration and the Anglo-American Rivalry over Revolutionary Hispanic America (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
This article reconstructs the genesis and consequences of President Monroe’s message of December 2, 1823, by studying the tormented relationship between the United States and Britain, and their tacit conflict for a “sufficient” strategic control over Spanish America’s political and commercial reconfiguration during the global war marking the final clash among the old Atlantic empires. We will first investigate Britain’s reactions to US official and unofficial policies as a driving force of informal imperialism in South America. We will then describe the two powers’ rivalry in unofficially supporting the liberation campaigns in South America and the impact of their indirect aid. Finally, we will retrace the origins of Monroe’s message in the initiatives of both powers to recognize Spanish-American independence, but also the US ambiguities on their hemispheric “doctrine”, with particular reference to Mexico. Here the prospect of a continental “empire” of republican freedom represented the detonator of a profound internal instability. Through entangled stories of British and US agents, the last sections consider the case of Texas as the terrain in which the British dream of a buffer against US expansion in the Americas faded.
Keywords: Hemispheric Dream; British American Rivalry; Spanish American Independence; Western Question; Mobility and Empires